Effect of Study-Duration and Time of Day on Multichannel Sleep Study Findings in Former Preterm Infants - Allison Sadowski; Naveed Hussain; Leonard I. Eisenfeld; Mariann Pappagallo; Janet Schwenn; Ted S. Rosenkrantz (Children)
Background/Objectives: Determine the appropriate duration for multichannel sleep studies in former preterm infants with cardio-respiratory events beyond term equivalent age. Hypothesis: A sleep study of 10 h will provide equivalent information compared to a 20-h study to detect significant cardio-respiratory abnormalities in this population. Methods: Single-center retrospective study of 50 infants with 20-h sleep study. Studies were evaluated for periodic breathing, obstructive, central, mixed apnea, desaturations, and bradycardia. Each study was partitioned into two 10-h epochs, compared to one another and the 20-h study. Results: Differences were detected at the level of individual sleep studies when each epoch was compared to each other and a total 20-h study. 10-h study missed 17–31% of breathing abnormalities detected over 20 h adjusted for study time. Group analysis showed no statistical difference in the number and duration of events between epochs. Conclusions: A 20-h sleep study improves the detection of breathing abnormalities missed with a 10-h study.